Book of the disappeared : the quest for transnational justice - Heath, Jennifer; Zahedi, Ashraf, 1947- (Ethnic conflict., 2023)
This book confronts worldwide human rights violations of enforced disappearance and genocide and explores the global quest for justice with contributions by scholars, practitioners, and artists.